Evolution of genetically determined generalized epilepsies - E. A. Morozova; F. I. Gusyakov (Эпилепсия и пароксизмальные состояния)
This article analyzes the available literature regarding the clinical manifestations, genetic determinants, prognosis and evolution of inherited generalized epilepsies. We describe the typical EEG characteristics and their correlations with negative prognostic factors. We also review studies on absence epilepsy of childhood, juvenile myoclonic epilepsy and epilepsy with generalized tonic-clonic seizures. Factors indicating a more severe course and outcome of the disease, and those indicating a more favorable development have been analyzed. Among those, age of the seizure onset, type of initial therapy, time passed before starting therapy and time before a response was seen, cognitive status, combination of seizures, abnormal discharges in EEG, and neurological deficit. The analysis shows that factors correlating with poor prognosis include the presence of more than one type of seizures, insufficient response to initial therapy, necessity of polytherapy and concomitant cognitive impairment.